Local two-atom correlations induced by a two-mode cavity under nonlinear media: Quantum uncertainty and quantum Fisher information - A.-B.A. Mohamed; E.M. Khalil; N. Metwally; H. Eleuch (Results in Physics, 2021)
The nonlinearity effect on the various formed quantum correlations between two atoms interacting locally with a bimodal cavity is explored in this work. The local quantum Fisher information, local quantum uncertainty, and negativity are used to investigate the quantum correlation’s sensitivity to the cavity modes characteristics. It is demonstrated that when the ratio of the Stark shift of the two modes increases, the atomic quantum correlations rise. During the time intervals of sudden death negativity entanglement, the three two-atom correlation quantifiers reveal that the two-atom system can contain local Fisher information and local uncertainty correlations. The Stark shift may be utilized to amplify the produced atomic correlation, while the Kerr-like medium can be used to suppress it. The regularity, the amount of generated atomic correlations, and their immunity to the Stark shift as well as the Kerr-like medium non-linearities are improved when the mean photon number is increased. As a result, the cavity modes’ nonlinear parameters might be utilized as a controller to optimize atomic quantum correlations.